Critical thermodynamic evaluation of the binary sub-systems of the core sulphate system Na2SO4–K2SO4–MgSO4–CaSO4. (March 2021) - Yazhenskikh, Elena; Jantzen, Tatjana; Kobertz, Dietmar; Hack, Klaus; Müller, Michael
Abstract: The binary subsystems of the quaternary system Na2 SO4 –K2 SO4 –MgSO4 –CaSO4 were thermodynamically assessed using the available experimental information including own thermochemical and structure measurements. Phase equilibria and thermodynamic properties of all six binary systems were properly considered. The modified associate species model was successfully applied for the description of the liquid phase while the mutual solubility between various sulphates in the solid state was treated with appropriate multi-sublattice models. The resulting new databank being compatible with the general oxide database was used for the representation of the thermodynamic properties in the binary systems including phase equilibria, activity and mixing data. The calculations are in good agreement with the experimental data. Highlights: Binary alkali-alkaline earth sulphate systems were thermodynamically assessed. Recent experimental data were included in the assessment. Modified associate species model was used for the liquid phase. Gibbs energy of double sulphates was generated for a first time. Calculated thermodynamic properties in good agreement with the experiments.